2020
DOI: 10.1002/cctc.202000152
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Dehydration of 1,4‐Butanediol over Mg−Yb Binary Oxides and the Mechanism Study

Abstract: In this study, MgÀ Yb binary oxides were synthesized using different MgO concentrations and investigated for the catalytic dehydration of 1,4-butanediol (BDO) into 3-buten-1-ol (BTO). The physicochemical properties of the catalysts were characterized by N 2 physisorption, X-ray diffraction, Raman spectroscopy, temperature-programmed techniques, and diffuse reflectance infrared Fourier transform spectroscopy. The MgÀ Yb binary oxides exhibited superior catalytic activity and better BTO selectivity compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…Likewise, it was reported that the addition of Yb to magnesium oxide increased the number of acid sites on the catalyst, yet maintaining a high concentration of basic sites. Overall, this contribution of both acidic and basic sites accounted for the performance of the catalyst …”
Section: Upgrading Of Polyolsmentioning
confidence: 98%
See 4 more Smart Citations
“…Likewise, it was reported that the addition of Yb to magnesium oxide increased the number of acid sites on the catalyst, yet maintaining a high concentration of basic sites. Overall, this contribution of both acidic and basic sites accounted for the performance of the catalyst …”
Section: Upgrading Of Polyolsmentioning
confidence: 98%
“…Overall, this contribution of both acidic and basic sites accounted for the performance of the catalyst. 525 2.4.5. Miscellaneous.…”
Section: 43mentioning
confidence: 99%
See 3 more Smart Citations